SOCIAL SUPPORT NETWORKS FOR YOUTHS AGING OUT OF RESIDENTIAL CARE TO PROMOTE POSITIVE TRANSITION OUTCOMES – A SCOPING REVIEW - Charity Pote; Glynnis Dykes; Shernaaz Carelse (Social Work/Maatskaplike Werk, 2022)
This scoping review provides the available evidence on support interventions and networks for youths aging out of child and youth care centres (CYCCs), and makes recommendations for best practice to alleviate the plight of youths leaving CYCCs. Thirteen databases were searched, resulting in the retrieval of 80 articles, 26 of which met the review criteria: English, full-text, peer-reviewed, open-access studies conducted between 2015 and 2020 on social networks and transitional services to youths aging out of residential care. Recommendations are made for policy changes, extending the age of eligibility and strengthening social support networks for youths transitioning into independent living.